English language as tool to promote touristic activity in machachi parish during the academic cycle april – august 2015 - Changoluisa Criollo, Marco Patricio (2015)
This research work was developed in order to increase tourism in Machachi parish, which is part of Mejia canton in the Pichincha province, using the English language as communicative base and improve tourism promotion through a website as an advertising platform. The local municipality currently provides information written in Spanish language that focuses on basic aspects that reduces its scope and projection to potential national and foreign tourists. While to present this information in English language, which is the most widespread language in the world, undoubtedly increases the scope and projection already mentioned….